2022
DOI: 10.1186/s13568-022-01440-8
|View full text |Cite
|
Sign up to set email alerts
|

What lies on macroalgal surface: diversity of polysaccharide degraders in culturable epiphytic bacteria

Abstract: Macroalgal surface constitutes a peculiar ecological niche and an advantageous substratum for microorganisms able to degrade the wide diversity of algal glycans. The degrading enzymatic activities of macroalgal epiphytes are of paramount interest for the industrial by-product sector and biomass resource applications. We characterized the polysaccharide hydrolytic profile of bacterial isolates obtained from three macroalgal species: the red macroalgae Asparagopsis taxiformis and Sphaerococcus coronopifolius (Rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…SignalP v5.0 was used to predict the signal peptides (Almagro Armenteros et al, 2019). Barbato et al (2022) identified polysaccharide lyases (PL) and glycoside hydrolases (GH) as the primary enzymes responsible for degrading algal polysaccharides. Table S2 presents data on PLs + GHs, while Table S1 shows the strain codes.…”
Section: Genome Comparisonmentioning
confidence: 99%
“…SignalP v5.0 was used to predict the signal peptides (Almagro Armenteros et al, 2019). Barbato et al (2022) identified polysaccharide lyases (PL) and glycoside hydrolases (GH) as the primary enzymes responsible for degrading algal polysaccharides. Table S2 presents data on PLs + GHs, while Table S1 shows the strain codes.…”
Section: Genome Comparisonmentioning
confidence: 99%
“…Red algae are widely distributed in marine environments and tend to be colonized by rich and diverse communities of bacteria, some of which may be cultured under lab-oratory conditions [1][2][3][4]. Many novel bacterial species associated with different red algae have been described in recent years.…”
Section: Introductionmentioning
confidence: 99%